Higher fungi in soils of coastal Arctic tundra plant communities - Laursen, Gary A. (Virginia Polytechnic Institute and State University, 1975)
Presence and abundance of filamentous soil mycelium was determined in North American coastal Arctic tundra soils near Barrow, Alaska. Soils were examined at one centimeter intervals from the surface to the depth of thaw, 0-24 cm, over a three year period during the International Biological Programme Tundra Biome study. Examined were 1217 soil samples, and 57,850 microscopic fields which clearly made this quantitative study of soil fungi the most comprehensive of its kind for tundra. Over 30 study plots were regularly sampled along a 1400 meter moisture dominated gradient. The plots were conveniently categorized into one of five principal habitats in polygonally dominated terrain. The five habitats were polygon troughs, rims, low centered basins, high centered and flattened polygon tops, and mesic tundra meadows. All plots were described vegetatively and physiographically. Presence of soil fungi was expressed in meters of mycelium per gram dry weight of soil (m/gdws) and grams per square meter to a 1 cm depth. Mycelium averaged 700 m/gdws and 1.05 g/m²/cm to 7 cm during the 1972-1974 study. Mycelium values ranged from 213 to 3504 rn/gdws and .34 to 8.11 g/m²/cm at the 1-2 cm depth, and from 76 to 445 m/gdws and .29 to 1.97 g/m²/cm at the 6-7 cm depth. Seasonal fluctuation of mycelium showed early season vernal highs followed by,an abrupt decline to mid season, a build up to a Fall peak concurrent with fungal fruiting and a general decline to season endings and freeze-up. Amplitudes of mycelium level fluctuation were greater and showed greater variation in surface soils, 1-2 cm, as contrasted to the deeper profile layers, 6-7 cm. Mycelium production rates showed that 1 m of initial mycelium gave rise to 2.7 m by season's end. Over 75 % of the fungal mycelium was concentrated in the upper 4-5 cm of the soil profile. The 2-4 cm depth was also the zone of maximum vascular plant root concentration. Low levels of resident mycelium were detected at 24 cm depths in all habitats that could be sampled to that depth. ...